2016
DOI: 10.1371/journal.ppat.1005732
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Architecture of Group A Streptococcal Necrotizing Soft Tissue Infections in the Mouse

Abstract: Host genetic variations play an important role in several pathogenic diseases, and we have previously provided strong evidences that these genetic variations contribute significantly to differences in susceptibility and clinical outcomes of invasive Group A Streptococcus (GAS) infections, including sepsis and necrotizing soft tissue infections (NSTIs). Our initial studies with conventional mouse strains revealed that host genetic variations and sex differences play an important role in orchestrating the severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…Interestingly, IL-1β proved to be an independent predictor for 30-day mortality. Further support for IL-1β as a potentially useful marker for NSTI was recently provided in a murine model of streptococcal NSTI, in which IL-1β response network was identified as a key network involved in modulating severity of streptococcal NSTI 34 . Another limitation to this study is the limited time of follow-up regarding amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-1β proved to be an independent predictor for 30-day mortality. Further support for IL-1β as a potentially useful marker for NSTI was recently provided in a murine model of streptococcal NSTI, in which IL-1β response network was identified as a key network involved in modulating severity of streptococcal NSTI 34 . Another limitation to this study is the limited time of follow-up regarding amputation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the bacterial and viral species under study are human pathogens. In recent years it was also shown that host genetic variations and sex differences have an impact on predisposition, severity, and outcome of infection ( Chella Krishnan et al, 2015 , 2016 ) While C57BL/6 and BALB/c mice are characterized by a higher resistance, DBA/2 strains are more susceptible and permissive to bacterial and viral strains ( Alymova et al, 2011 ; Chella Krishnan et al, 2015 , 2016 ). In addition, transmission of IAV and bacteria is inefficient in adult mice, thus requiring alternative animal models, including neonatal mice or ferrets ( Diavatopoulos et al, 2010 ; McCullers et al, 2010 ).…”
Section: Suitable In Vivo Models For Mimicking Resmentioning
confidence: 99%
“…An HLA-II tg mouse model of NSTI for Treg analysis. In order to understand the mechanisms and disease signatures underlying NSTI, we used a forward-genetics approach in an advanced recombinant inbred BxD mouse model specifically optimized for NSTI (24). To elucidate the role of HLA-II alleles and their influence on T-effector and Treg polarization during NSTI, we used a subcutaneous skin infection model of GASmediated NSTI in HLA-II transgenic mice that mimic lesions and inflammatory responses observed in humans.…”
Section: Resultsmentioning
confidence: 99%
“…We used the clinical isolate M1 GAS 2006 for the in vivo studies. GAS 2006 was grown under static conditions in Todd-Hewitt broth supplemented with 1.5% yeast extract for 17 h at 37°C (11,24,41). The bacteria were harvested by centrifugation, washed three times with sterile endotoxin-free Dulbecco's phosphate-buffered saline (DPBS), and resuspended in DPBS.…”
Section: Methodsmentioning
confidence: 99%